Design and performance analysis of a compact magnetorheological valve with multiple annular and radial gaps. (June 2015) - Imaduddin, Fitrian; Mazlan, Saiful Amri; Zamzuri, Hairi; Yazid, Izyan Iryani Mohd
A novel concept of a compact magnetorheological valve is proposed based on the advance characteristics of magnetorheological fluid. The structural design consists of a meandering pattern formed by multiple annular and radial gaps in order to extend the flow path length of magnetorheological fluid. Extending the flow path of magnetorheological fluid is important in order to increase the density of effective area, so that the rheological properties of magnetorheological fluid can be widely regulated in a small size magnetorheological valve. The main objective of this article is to show that the pressure drop as one of the key performance indicators in a magnetorheological valve can be significantly increased using multiple annular and radial gaps configuration. In order to demonstrate the magnetorheological valve performance, simulation work using magnetic simulation software called finite element method–based software for magnetic simulation is conducted and combined with the pressure drop calculation using the derived magnetorheological valve model. Simulation results show that the magnetorheological valve with multiple annular and radial gaps is able to improve the achievable pressure drop. The discussion on the effect of gap size variations on the achievable pressure drop and the operational range of magnetorheological valve is also presented.